Field notes contributed by Peter C. Petersen, fall 1996 - Petersen, Peter C.et al (1996)
List of birds and locations contributed by Peter C. Petersen with observers Mary Lou Petersen, Kelly McHay, Lewis Blevins and Corey Blevins. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed/flatbed